AB0996 Increased release time of diclofenac loaded into a cross-linked hyaluronic acid hydrogel. (23rd January 2014) - Dall, O.M.; Maltesen, M.; Larsen, M.; Longin, F.
Abstract : Background: Hyaluronic acid (HA) is a natural linear and unbranched polysaccharide belonging to the class of non-sulphated glycosaminoglycans and it is composed of beta-1, 3-N-acetyl glucosamine and beta-1, 4-glucuronic acid repeating disaccharide units. HA is ubiquitous in human and animal tissues 1 and is recognized as a high-value biopolymer with numerous proven and marketed applications within the cosmetic, biomedical and pharmaceutical fields. However, HA injected in the body is typically degraded rapidly limiting the long term effects of the polymer. In this work HA produced by fermentation of Bacillus subtilis strain, has been cross-linked with divinyl sulfone (DVS) to produce hydro gels suitable for pharmaceutical applications. Diclofenac is used as a model drug and loaded into the cross-linked HA hydrogel yielding a depot sustained release formulation targeted towards osteoarthritis treatment. Objectives: To determine the slow release properties of a HA based hydrogel loaded with diclofenac. Methods: The HA was produced by Novozymes Biopharma DK A/S by fermentation of Bacillus subtilis . The average molecular weight of the starting material was 0.85 MDa. The commercial diclofenac formulation was Voltaren® (Novartis International AG). Hydro gels were prepared with a DVS/HA weight ratio of 1:10 with a final HA concentration of 1.4 w/w % 2 . HA was dissolved in 0.2 M NaOH and stirred for 1 h yielding a 4% (w/v) HA solution. DVS was added to the HA solution in a weight ratio of 1:10. The mixture was stirred vigorously for 5 min and then incubated for 1 h at room temperature. The cross-linked HA hydro gels were swollen in PBS buffer yielding a 1.4% w/v hydrogel with a pH of 7.4. The hydro gels were freeze-dried after cross-linking. Diclofenac was dissolved in PBS buffer pH 7.4 and swelled into the freeze-dried hydro gels. The release of diclofenac from the cross-linked HA hydro gels was assessed by dissolution using a closed loop system configuration (SOTAX CE7smart) and USP 4 dissolution method with 22.4 mm cells. 100 mL PBS buffer pH 7.0 was used as medium equilibrated at 37 °C. The flow rate was set to 4 mL/min and a high stirring speed was used. Diclofenac was detected on-line with UV absorbance at 276 nm. A total of 20 mg of diclofenac was loaded in the cells and is considered as total drug load in relation to both Voltaren and hydrogel analysis. Results: The release of diclofenac from the hydrogel formulation was followed by UV detection at 276 nm. The release profiles of a commercial diclofenac formulation (Voltaren®) and the cross-linked HA hydrogel loaded with diclofenac were shown to be significant different. A complete drug release was achieved after 10 minutes for the commercial diclofenac formulation, on the contrary cross-linked HA hydrogel from Novozymes retained diclofenac up to 10 hours. Conclusions: In this work we showed that incorporation of diclofenac in a HA hydrogel increases the drug release from less than 10 minutes to approximately 10 hours. These findings support development of a depot sustained release formulations, targeted towards osteoarthritis treatment and consisting of cross-linked HA hydro gels and diclofenac. References: Liao. Y.-H; Jones, S.A.; Forbes, B.; Martin, G.P.; Brown, M.B. Drug Delivery 2005, 12, 327-342. Longin, F.; Schwach-Abdellaoui, K., WO/2006/056204. Disclosure of Interest: None Declared